The Influence of Acoustic Stimuli on “Walking Straight” Navigation by Blindfolded Human Subjects - Wersényi, Gy.; Répás, J. (Acta Technica Jaurinensis, 2012)
Navigation of blindfolded sighted participants was tested in a 40-m freespace outdoor environment with and without external acoustic beacons. The common everyday observation about circling or veering from the straight line during walking without vision was tracked by means of a GPS device. 120 subjects participated from 19 to 83 years of age. Results are presented for normal walkings (no acoustic target), and for walkings with two different acoustic targets (click-train and white noise). This investigation supports the necessity of an external reference for walking in a straight course, furthermore, that different kind of acoustic stimuli can be used, and finally it serves for a comparative basis for further investigations with blind participants.